Peran Guru Bimbingan Konseling SD Dalam MeningkatkanKarakter Mandiri Dan Percaya Diri Pada Siswa Kelas IV Di SD Negeri 01 Tempuran, Simo Boyolali - Nurjanah, Reski, Dr. Achmad Fathoni, S.E., M.Pd (2017)
The aims of this study is to describe 1) The role of guidance and counseling teacher in Elementary School in improving independent and confidence character, identify 2) Steps of guidance and counseling teacher in improving independent andgconfidence character, identify 3) Barriers of guidance and counseling teacher in improving independent and confidence character, identify 4) The efforts of guidance and counseling teacher in improving independent and confidence character. The kind of this research is qualitative. The used of collecting data technique are interview, documentation, and observation. Data were analyzed through analyzed interaktif. Techniques of data absence examination doing by triangulation technique. Results of this research show that 1) The role of guidance and counseling teacher in Elementary School in improving independent and confidence character involve: a) problem solving, b) guide, c) motivate, 2) Steps of guidance and counseling teacher in improving independent and confidence character involve: a) problem identification; look at students do their task, their result, b) diagnosis; students feels they can't before try, their habit in their family always be served, c) prognosis; given task, monitored, given spirit, d) therapy; doing an approach by digging information which makes student not independent e) evaluation; treatment which was done almost successful, 3) Barriers of guidance and counseling teacher in improving independent and confidence character involve: a) facilities and infrastructures; availability guidance and counseling room, b) time and task; service done at break time 15-20 minutes, c) intellectual competence; able to understand the behavior and needs of students, d) communication competence; not fully able to communicate with students. 4) Effort of guidance and counseling teacher in Elementary School in improving independent and confidence character involve: a) increased confidence and independence: given responsibility for not crowded in the classroom when the teacher is not in, and given task to collected in teacher table,b) motivation; giving awareness that task is important, giving praise and reward.